PENGUJIAN PENGARUH CAPITAL STUCTURE PADA DEBT POLICY (Studi Empiris pada Perusahaan Manufaktur di Indonesia) - D.L, Wuryaningsih (Benefit, 2004)
This research aim to test the impact of capital structure to company debt policy. The capitalstructure consisted by insider ownership, institutional investor, and shareholder dispersion. This researchuse sample of all manufacturing business which enlisted in Jakarta Stock Exchange during year ofl999 - 2002. result of partial test indicated that shareholder dispersion variable have a significant effectto company debt policy. Examination by simultaneously indicate that all component of capital structurehave a significant effect on negativity to company debt policy. Equally, all variables mirroring expense ofagent serve to purpose of instrument of determinant of debt policy to minimize agency cost.